Perbedaan Kebutuhan Morfin PCA Pasca Laparatomi antara Infiltrasi Ketamin Dan Infiltrasi Levobupivakain - Heri Dwi Purnomo; Ardana Tri Arianto; Arif Wahyu Widayat (Faculty of Medicine, Universitas Padjadjaran, 2021)
Penanganan nyeri akut yang tidak adekuat merupakan faktor risiko terjadin nyeri kronik dan komplikasi lainnya. Metode yang efektif dan efisien mengontrol nyeri akut yang berat adalah infiltrasi tepi luka operasi. Penelitian ini bertujuan untuk mengetahui efektivitas infiltrasi ketamin dan levobupivakain dalam mengurangi kebutuhan morfin patient controlled analgesia (PCA) pascalaparatomi. Penelitian ini merupakan uji klinik acak tersamar tunggal yang dilakukan di RSUD Dr. Moewardi Surakarta pada bulan Agustus 2018. Sampel terdiri atas 30 subjek yang dilakukan operasi laparatomi dengan anestesi umum yang dibagi menjadi 3 kelompok, yaitu kelompok infiltrasi levobupivakain, infiltrasi ketamin, dan infiltrasi saline. Semua pasien mendapatkan morfin PCA pascaoperasi. Setelah itu dinilai jumlah penggunaan morfin dan efek mual-muntah pascaoperasi, dan efek samping tindakan infiltrasi. Penggunaan morfin PCA pada kelompok ketamin rerata 2,20+1,32 mg, pada kelompok levobupivakain penggunaan morfin rerata 5,80+1,03 mg, dan pada kelompok NaCl penggunaan morfin rerata 10,00+1,76 mg. Uji statistik Kruskal Wallis didapatkan perbedaan yang signifikan penggunaan morfin PCA antara pasien kelompok ketamin, levobupivakain dan NaCl (p<0,05). Simpulan penelitian ini bahwa infiltrasi ketamin mengurangi nyeri pascalaparatomi lebih baik dibanding dengan infiltrasi levobupivakain dan saline.Differences in Post-laparotomy PCA Morphine Needs between Ketamine Infiltration and Levobupivacaine Infiltration Inadequate acute pain management is a risk factor for chronic pain and other complications. Laparotomy is a painful procedure with severe acute pain. Patient controlled analgesia (PCA) morphine use in acute pain control is promoted for efficiency and effectiveness. Wound infiltration is also effective in reducing acute pain. This study aimed to determine the effectiveness of ketamine and levobupivacaine wound infiltration in reducing the need for post-laparotomy PCA morphine. This study used a single-blind randomized clinical trial at RSUD Dr. Moewardi Surakarta on 30 subjects who underwent laparotomy and met the inclusion criteria. The samples were divided into three groups: wound infiltration with levobupivacaine, wound infiltration with ketamine, and wound infiltration with saline. All patients received standard general anesthetic treatment and were then evaluated for the total use of PCA morphine. It also assessed the effects of postoperative nausea-vomiting and the side effects of wound infiltration. The average PCA morphine use in the ketamine group was 2.20+1.32 mg. In the Levobupivacaine group was 5.80+1.03 mg, and in the NaCl group was 10.00+1.76 mg. Kruskal Wallis statistical test obtained p-value=0.000 (p<0.05), which means that there was a significant difference in PCA morphine use after 24 hours between the three groups. No complication occurred with the three-group wound infiltration. Thus, there is a significant difference in the use of PCA morphine between wound infiltration with ketamine and wound infiltration with levobupivacaine and with saline infiltration. Ketamine wound infiltration can be used effectively to reduce post-laparotomy pain.